Repetitive DNA Mapping in Five Genera of Tree Frogs (Amphibia: Anura) from the Atlantic Forest: New Highlights on Genomic Organization in Hylidae - Souza, Késsia Leite; Melo, Silvana [UNESP]; Peixoto, Marco Antônio; Travenzoli, Natália Martins; Feio, Renato Neves; Dergam, Jorge Abdala (Karger Publishers, 2024)
Introduction: The tribes Cophomantini, Scinaxini, and Dendropsophini are anurans that belong to Hylidae, with wide distribution in tropical and subtropical regions around the world. The taxonomy and systematics of this family remain in a state of ongoing revision. Previous cytogenetic analyses of genera Boana, Bokermannohyla, Ololygon, Scinax, and Dendropsophus described some karyotypic characters such as conventional staining, C-banding and NORs, and FISH with specific probes. Methods: This study describes for the first time the karyotypes of four species: Bokermannohyla ibitipoca, Ololygon luizotavioi, Dendropsophus bipunctatus, and Dendropsophus ruschii. Furthermore, wemap CA(15) and CAT(10) microsatellite sites for the aforementioned species and six more species from the same genera for insight into the chromosomal evolution within the subfamily Hyalinae. Results: B. ibitipoca and O. luizotavioi had 2n = 24 and karyotypic formulas 18m + 4sm + 2st and 8m + 12sm + 4st, while D. bipunctatus and D. ruschii showed 2n = 30 and karyotypic formulas 12m + 12sm+ 4st + 2t and 10m + 10sm + 6st + 4t, respectively. The diploid numbers and karyotypic formulas revealed here follow the previously reported trend for Hylidae, except B. ibitipoca has a particularity of eight metacentric chromosomes, more than what is commonly found in species of this genus. The microsatellites probes CA(15) and CAT(10) had markings accumulated in blocks in the centromeric, pericentromeric, and terminal regions that were more specific for some species, as well as markings scattered along the chromosomes. We present a comprehensive review table of current data on cytogenetics of these genera. Conclusion: Our findings showed that the karyotypes of the hylids studied here majority fit the postulated conserved diploid number (2n = 24) and morphological chromosome patterns, while the mapping of the microsatellites enabled us to detect differences between species that share similar chromosomal morphologies.
Keywords: Chromosomal evolution; Fluorescent in situ hybridization; Microsatellite; Repetitive DNA; Tandem repeats